Intelligent Dip Test Method for Performance Analysis of Polymeric Coating Material - H., Rajini; Ravi , K. N.; N., Vasudev (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Porcelain and glass insulators are coated with Room temperature vulcanizing (RTV) silicone rubber coating due to its excellent leakage current suppression characteristics to overcome the pollution problem. The reliability of leakage current on various samples of the glass plate sample is studied and reported. In this study, the withstand capability of RTV coated insulators for pollution were evolved, and based on the experimental results long term aging performance of different RTV coated insulators was evaluated